The perspective of antibiotic therapeutic challenges of brucellosis in the Middle East and North African countries: Current situation and therapeutic management. Issue 5 (13th March 2022) - Wareth, Gamal; Dadar, Maryam; Ali, Haytham; Hamdy, Mahmoud E. R.; Al‐Talhy, Ahmad M.; Elkharsawi, Ahmed R.; Tawab, Ashraf A. Abd El; Neubauer, Heinrich
Abstract: Brucellosis is among the most prevalent zoonotic infections in Middle Eastern and North African (MENA) countries, critically impacting human and animal health. A comprehensive review of studies on antibiotic susceptibility and therapeutic regimes for brucellosis in ruminants and humans in the MENA region was conducted to evaluate the current therapeutic management in this region. Different scientific databases were searched for peer‐reviewed original English articles published from January 1989 to February 2021. Reports from research organizations and health authorities have been taken into consideration. Brucella melitensis and Brucella abortus have been reported from the majority of MENA countries, suggesting a massive prevalence particularly of B. melitensis across these countries. Several sporadic cases of brucellosis relapse, therapeutic failure, and antibiotic resistance of animal and human isolates have been reported from the MENA region. However, several studies proved that brucellae are still in‐vitro susceptible to the majority of antibiotic compounds and combinations in current recommended World Health Organization (WHO) treatment regimens, for example, levofloxacin, tetracyclines, doxycycline, streptomycin, ciprofloxacin, chloramphenicol, gentamicin, tigecycline, and trimethoprim/sulfamethoxazole. The current review presents an overview on resistance development of brucellae and highlights the current knowledge on effective antibiotics regimens for treating human brucellosis.